Financial Management Process of Pesantren Nurul Muhibbin Tanah Laut - Muhammad Khofi; Noor Amelia; Karolina (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Pesantren Nurul Muhibbin Tanah Laut, which is classified as a new Islamic boarding school, was founded in 2018, and as such, it requires significant input and assistance in resolving issues, particularly those relating to financial management and accounting information systems. If an error is made, not only social sanctions are imposed, but also legal sanctions; this must be a bright spot in the pesantren's financial management. This research employs a qualitative approach in the hope of identifying financial phenomena that can be used as material for joint evaluation. The study examines financial planning, implementation, supervision, and reporting phenomena. This financial process will be visualized as a flowchart in the hope that the relationship between the various components is obvious. Several of the findings in this study indicate that financial planning has been successful in terms of implementing a priority scale, deliberatively forming APBPP, and developing plans to strengthen pesantren financial management. The implementation process has not perfectly implemented the principle of accountability and generally continues to make ineffective cash payments, the supervisory process continues to violate the principles of organizational adjustment and responsibility, and the management accounting process and reporting continue to have numerous shortcomings, such as conventional accounting processes and the use of accrual accounting. The pesantren currently lacks a flow chart that adequately depicts the financial management process.